Effects of glass ionomer sealants in newly erupted first molars after 5 years: a pilot study - Taifour D, Frencken JE, van 0t Hof MA, Beiruti N, Truin G-J (Blackwell Synergy, 2003)
The aim of the study was to investigate the caries-preventive effect of high-filled glass ionomer sealant in newly erupted first molars in a high-risk group.